SOCIAL IMPORTANCE OF RHEUMATIC DISEASES IN RUSSIA - V A Nassonova; O M Folomeyeva; Sh Erdesz (Научно-практическая ревматология, 2002)
Quantitative (primary and general morbidity) and qualitative (labor losses, invalidization, price of the diseasis, living standard of pts) parameters characteristic for muscle-skeletal and connective tissue diseases (MSD) in Russia for the last decade are analyzed. It is demonstrated that these diseases present serious social problem, reducing economic, labor, defense and psychological potential of Russia.